肺部肿瘤射频消融治疗的临床应用与进展 (Zhongguo Fei Ai Za Zhi, 2010)
Lung cancer is the leading cause of cancer-related mortality worldwide. In recent years, radiofrequency ablation (RFA), as a minimally invasive therapy, has been increasing utilized as a non-surgical treatment option for patients with primary and metastatic lung tumors, and great advances have been achieved. The assessment of response after RFA is challenging, and we recommend the use of CT scans, MRI scans and PET scans to assess response rate. The purpose of the article is to review the principles, experimental background, clinical application and response in the treatment of lung neoplasms.